Toxicological risk assessment of mechanical-chemical vs. chemical weed control techniques in sugar beet in Germany using SYNOPS-GIS - Fishkis, Olga; Strassemeyer, Joern; Pöllinger, Franz; Roß, Christel Anne; Koch, Heinz-Josef (Frontiers in Agronomy, 2024)
Introduction. The EU Farm to Fork strategy aims to reduce the use of pesticides and associated toxicological risks. However, the risks coming along with currently available alternatives to chemical weed control in sugar beet have not yet been evaluated. Therefore, the aim of this study was to determine the toxicological risks to arthropods, aquatic and soil organisms caused by mechanicalchemical in comparison to conventional chemical weed control in sugar beet.The risk assessment was performed using SYNOPS-GIS, a process-based model calculating the environmental fate of pesticides and the exposure risk to arthropods, aquatic and soil organisms.Results and Discussion. Overall, broadcast spraying of conventional herbicides caused low to very low toxicological risks in most regions and years in Germany. Nevertheless, there were considerably higher risks to aquatic and soil organisms from conventional broadcast spraying in northern Germany than in other regions of Germany. With conventional herbicides, mechanical-chemical weed control reduced toxicological risks proportionally to the reduction in application amount. In contrast, band spraying of the new herbicide with the active ingredients foramsulfuron and thiencarbazone-methyl caused an aquatic risk as broadcast spraying with conventional herbicides, although the application rate was 120 times lower. This was due to high toxicity of both active ingredients of the new herbicide to water plants.Conclusions. Thus, not only the application amount of herbicides but also environmental toxicity should be included in assessment approaches such as the EU "Harmonized Risk Indicator".